Analysis of Textbook “Ilmu Saraf Untuk Pemula” Third Edition Writen by Abu Razin and Ummu Razin (Development Textbook Principles) - Afdhal Fikri Mirma; Talqis Nurdianto; Zainal Abidin Hajib (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This article aimed to analyze the book